2013
DOI: 10.1098/rsfs.2012.0072
|View full text |Cite
|
Sign up to set email alerts
|

The PredictAD project: development of novel biomarkers and analysis software for early diagnosis of the Alzheimer's disease

Abstract: One contribution of 25 to a Theme Issue 'The virtual physiological human: integrative approaches to computational biomedicine'. Alzheimer's disease (AD) is the most common cause of dementia affecting 36 million people worldwide. As the demographic transition in the developed countries progresses towards older population, the worsening ratio of workers per retirees and the growing number of patients with age-related illnesses such as AD will challenge the current healthcare systems and national economies. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…These include software applications that provide practical information for those caring for dementia patients (e.g., Dementia Support by Swedish Care International, Alzheimer’s and Other Dementias Daily Companion, MindMate) as well as tools used for mobile cognitive screening (e.g., MOBI-COG, Mobile Cognitive Screening, Dementia Screener, Sea Hero Quest, CANTAB). In addition, CDSSs, designed to aid clinical decision making by adapting computerized clinical practice guidelines to individual patient characteristics or integrating machine learning methodologies for pattern recognition, have been recently gaining more interest in expediting dementia diagnosis and disease management (Antila et al, 2013, Frame, LaMantia, Bynagari, Dexter, & Boustani, 2013, Lindgren, 2011, Lindgren, Eklund, & Eriksson, 2002). It has been shown that such systems are more sensitive in detecting an early-stage disease and more objective than diagnostic decisions made by a single practitioner (Moja et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These include software applications that provide practical information for those caring for dementia patients (e.g., Dementia Support by Swedish Care International, Alzheimer’s and Other Dementias Daily Companion, MindMate) as well as tools used for mobile cognitive screening (e.g., MOBI-COG, Mobile Cognitive Screening, Dementia Screener, Sea Hero Quest, CANTAB). In addition, CDSSs, designed to aid clinical decision making by adapting computerized clinical practice guidelines to individual patient characteristics or integrating machine learning methodologies for pattern recognition, have been recently gaining more interest in expediting dementia diagnosis and disease management (Antila et al, 2013, Frame, LaMantia, Bynagari, Dexter, & Boustani, 2013, Lindgren, 2011, Lindgren, Eklund, & Eriksson, 2002). It has been shown that such systems are more sensitive in detecting an early-stage disease and more objective than diagnostic decisions made by a single practitioner (Moja et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous EEG studies of conversion from mild cognitive impairment to Alzheimer's disease have been conducted (Jelic et al, 1996, 2000; Huang et al, 2000; Stam et al, 2003; Schoonenboom et al, 2004; Rombouts et al, 2005; Babiloni et al, 2006, 2011; Kwak, 2006; Rossini et al, 2006, 2008; Lehmann et al, 2007; Moretti et al, 2007a, b, 2008, 2011; Luckhaus et al, 2008) mainly using biomarkers such as spectral measures and synchronization between brain regions. Machine-learning techniques have been used to explore differences between MCI and AD with varying success (Huang et al, 2000; Bennys et al, 2001; Prichep et al, 2006; Buscema et al, 2007; Lehmann et al, 2007; Prichep, 2007; Rossini et al, 2008), however, only few studies have tried to predict the conversion from MCI to AD (Prichep et al, 2006; Prichep, 2007; Antila et al, 2013). Many studies typically focus on a small number of biomarkers (on the order of 15 marker values), and some do not have adequate validation of their results on independent groups.…”
Section: Introductionmentioning
confidence: 99%
“…According to Antila et al [1], nowadays Alzheimer's disease (AD) is the most common cause of dementia. The World Health Organization reported in 2012 that 36.5 millions of persons suffer from dementia in the world [2], that is 0.5 % of the total population (data from 2010).…”
Section: Introductionmentioning
confidence: 99%